THE EFFECT OF ISLAMIC HUMAN DEVELOPMENT INDEX ON POVERTY LEVEL IN BIREUEN DISTRICT PERIOD 2000-2017 - Muhammad Reza; Hijri Juliansyah; Yulius Dharma (Journal of Malikussaleh Public Economics, 2018)
The study entitled "The Influence of the Islamic Human Development Index Against Poverty Levels in Bireuen District 2000-2017". The data used in this study are secondary data in the form of time series data from 2000-2017 obtained from BPS Bireuen. Data were analyzed by multiple regression methods. The results of the research based on Index ad-dien show that the crime rate has a significant negative effect on the poverty level, based on Index an-nafs shows that life expectancy does not have a significant effect on poverty levels, based on Index al-'aql shows that the average length of school has a negative effect significant to the level of poverty, Index an-nasl shows that the birth rate does not affect the level of poverty and expenditure per capita population does not affect the level of poverty in Bireuen District. This reflects that although per capita expenditure remains high, it will not increase the number of poor people in Bireuen District.